A Review on Cultivation of Hop Shoots (Humulus lupulus) - Nath, Mausum Kumar; Dutta, Shourov; Datta, Himadri Shekhar (International Journal of Economic Plants, 2022)
Humulus lupulus or Hop shoots is a hardy dioecious perennial climbing plant that belong to the family Cannabinaceae. It is well-known in the brewing business for its high value. The Strobiles or ‘cones’ of the female plant are used for commercial purposes, whilst the male plants are used only for hybridization. Hop shoots is a delicate vegetable in most of the European countries and fetch a very high price in the market. The plant can grow in a wide range of soil conditions, from light sandy to clay. Hop shoots can be propagated vegetatively through stem/leaf cuttings, rhizomes or asexually. Hop shoots find a variety of uses in the field of medicine, industry, food and fiber. Presently, hop shoots are cultivated in nearly 15 nations around the world, with the United States being the leading producer. The present review deals with the reproductive biology, taxonomical description, cultivation, uses, marketing, commercial approaches and future aspects of the crop